The Study of Visionary Leadership with Change Management of School Administrators under the Secondary Education Service Area Office 36 (Chiang Rai - Phayao) - โสภโณทัย สุภาพร (Trends of Humanities and Social Sciences Research, 2019)
The objectives of this research were to study visionary leadership and change management of school administrators, the comparision of visionary leadership and change management of school administrators and the correlation between visionary leadership with change management of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao). The representative sample were 451 people consists of 111 school administrators and 340 teachers under the secondary education service area office 36 (Chiang Rai - Phayao) in 2013 academic year. The research instrument was questionnaire. The data were analyzed by mean, standard deviation, t-test Independent, one - way ANOVA and Pearson’s product moment correlation coefficient. The research results were as follows: Visionary leadership of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao) were in high level. Change management of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao) were in high level. Visionary leadership and change management of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao) compare classified by education level, the duty position and work experience of the results were as follows 3.1 Visionary leadership of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao) compare classified by education level and the duty position there was significantly difference at 0.01 level but work experience was not significantly difference. 3.2 Change management of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao) compare classified by education level and the duty position there was significantly difference at 0.01 level but work experience was not significantly difference. The correlation between visionary leadership with change management of school administrators under the secondary education service area office 36 (Chiang Rai - Phayao) was in the same direction in high level means If school administrators have high visionary leadership, change management of school administrators will be in high level, too.